PRIMUS BASIN - A MODEL FOR OIL EXPLORATION - Proedrou, P.; Papaconstantinou, M. C. (Bulletin of the Geological Society of Greece, 2004)
An extentional tectonic led to the formation of the basin along marginal listric faults. The fast subsidence created the frame for the accumulation of a thick section of miocene, pliocene and quaternary deposits amounted to 5000 meters and resulted to the good preservation of the organic matter as source for the oil generation. The existence of anticlines and other types of traps around the deepest part of the basin where the oil generation took place is another important factor for discovering hydrocarbons. The growth fault activation led to the formation of roll over anticlines in front of them. Stratigraphie oil bearing traps do also exist. The thick salt layers that were deposited during the upper miocene following the isolation of the basin from the open sea contributed to the reduction conditions in it. Moreover this salt cap rock holds the whole oil migration below it and prescribes the stratigraphie level for the prospects. The short distance between the generation area and the surrounded fault and statigraphic traps accelerated the migration and trapping of the hydrocarbons. The strong relief of the basin due to the fast subsidence led to the extend deposition of turbiditic sediments that form the reservoirs for the majority of the fields.The good knowledge of the geological evolution of the basin and the geochemical processes which take place states the best prepositions for a successful hydrocarbons exploration.